2022
DOI: 10.1088/1748-9326/ac5b3a
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of forest growth and carbon sequestration to heat and drought in the Alps

Abstract: Climate change is expected to increase both the frequency and the intensity of climate extremes, consequently increasing the risk of forest role transition from carbon sequestration to carbon emission. These changes are occurring more rapidly in the Alps, with important consequences for tree species adapted to strong climate seasonality and short growing season. In this study, we aimed at investigating the responses of a high-altitude Larix decidua Mill. forest to heat and drought, by coupling ecosystem- and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 88 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…By adjusting the k max to better represent the transpiration response we may be able to identify the timing of important physiological processes (e.g., leaf shedding) that differ between the VC and RC. In this way, we may be able to better understand the significant changes in different ecosystem processes triggered by intense dry periods (Oddi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By adjusting the k max to better represent the transpiration response we may be able to identify the timing of important physiological processes (e.g., leaf shedding) that differ between the VC and RC. In this way, we may be able to better understand the significant changes in different ecosystem processes triggered by intense dry periods (Oddi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By adjusting the k max to better represent the transpiration response we may be able to identify the timing of important physiological processes (e.g., leaf shedding) that differ between the VC and RC. In this way, we may be able to better understand the significant changes in different ecosystem processes triggered by intense dry periods (Oddi et al, 2022).…”
Section: Addressing the Plant Hydraulic Traits: Homogeneity Versus Di...mentioning
confidence: 99%
“…More recently, the increasing availability of multi-year records of ecosystem productivity measurements from eddy-covariance (EC) stations in forests has allowed researchers to assess the association between inter-annual variability of aboveground woody biomass accumulation and gross or net primary productivity (GPP and NPP). Such associations have been very variable among different sites (Babst et al 2014) and studies, ranging from not significant (Rocha et al 2006, Delpierre et al 2016, Pappas et al 2020, Oddi et al 2022 to highly positively significant (Xu et al 2017, McKenzie et al 2021, Metsaranta et al 2021. In addition, Teets et al (2018) and Tei et al (2019) found significant positive associations, but observed that annual tree biomass increment lagged one year behind net ecosystem production (NEP) and GPP, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in forest EC sites have used tree-ring width (TRW) to estimate biomass growth (McKenzie et al 2021, Oddi et al 2022. Tree rings are a unique source of information, providing annually resolved measures of tree radial growth over long time periods (Speer 2010).…”
Section: Introductionmentioning
confidence: 99%